Artificial insemination as a tool to improve guinea fowl reproductive performance - Atawalna, Joseph; Kagya-Agyemang, James Kwame; Kwenin, William Kwajo Jimah (The Faculty of Veterinary Medicine of Syiah Kuala University, 2025)
Background and Aim: Guinea fowls are known for their low reproductive efficiency under natural mating conditions, which limits their potential for intensive production. This study aimed to evaluate the effect of artificial insemination on the reproductive performance of Guinea fowls as a strategy to enhance fertility and hatchability outcomes.Materials and Methods: A total of one hundred and fourteen (114) adult Guinea fowls were randomly assigned to three treatment groups. The first group consisted of Guinea fowls (GFs) naturally mated in a ratio of one (1) male to four females (4) in six replicates. In contrast, the second and third groups consisted of twenty-four (24) Guinea hens, artificially inseminated with 0.03 ml fresh undiluted Guinea cock semen and 0. l ml Guinea cock semen diluted (1:3) with Ringers lactate solution. Semen was collected once weekly from GCs trained for semen collection and used to artificially inseminate Guinea hens by the intra-vaginal method using a graduated 1ml syringe. Eggs were collected from the treatment groups from day two (2) to day seven (7) post-AI, processed, and then incubated. At the end of twenty-eight (28) days of incubation, the number of keets hatched per treatment group was counted. The unhatched eggs were broken open to determine infertile eggs and embryonic mortality.Results: The results from the study show that fertility (%), fertile hatchability (%), and total hatchability (%) were significantly higher in artificially inseminated Guinea fowls than in those naturally mated, while embryonic mortality was similar in all treatment groups.Conclusion: Artificial insemination improved Guinea fowl reproductive performance. It is recommended that artificial insemination be implemented as part of intensive Guinea production